Do not do in COPD: consensus statement on overuse - Villar-Álvarez, Felipe (Int J Chron Obstruct Pulmon Dis, 2018)
BACKGROUND: To identify practices that do not add value, cause harm, or subject patients with chronic obstructive pulmonary disease (COPD) to a level of risk that outweighs possible benefits (overuse). METHODS: A qualitative approach was applied. First, a multidisciplinary group of healthcare professionals used the Metaplan technique to draft and rank a list of overused procedures as well as self-care practices in patients with stable and exacerbated COPD. Second, in successive consensus-building rounds, description files were created for each “do not do” (DND) recommendation, consisting of a definition, description, quality of supporting evidence for the recommendation, and the indicator used to measure the degree of overuse. The consensus group comprised 6 pulmonologists, 2 general practitioners, 1 nurse, and 1 physiotherapist. RESULTS: In total, 16 DND recommendations were made for patients with COPD: 6 for stable COPD, 6 for exacerbated COPD, and 4 concerning self-care. CONCLUSION: Overuse poses a risk for patients and jeopardizes care quality. These 16 DND recommendations for COPD will lower care risks and improve disease management, facilitate communication between physicians and patients, and bolster patient ability to provide self-care.